The Effects of Albanian Terrorism in Kosovo and Metohija - Stevanović, Obrad M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The very first ideas about secession of Kosovo and Metohija of the Republic of Serbia and the use of violence in achieving them appeared immediately after the First Balkan War (1912). The key pillars of this, secessionist motivated violence in Kosovo during and after the wars of liberation of Serbia (1912 and 1918). And between the two world wars, were kachach, during and after World War II that were ballistic groups of Albanian extremists. Violence based on their tradition, with unforeseeable serious consequences for vital interests of the Republic of Serbia, escalated in the last decade of the twentieth century, violence Albanian extremist group called the Kosovo Liberation Army (KLA), supported by influential members of the international community. In many papers, the analysis of the specific objectives, the holders - active entities, resources, facilities attack - passive subjects and consequences, as constituent elements of that violence, confirmed his terrorist character of the KLA as a terrorist profile of its key holder. In this regard, the work is the result of research in which the author, as a consequence of the analysis of the constituent elements of Albanian terrorism in Kosovo and Metohija, the end of the last century and the beginning of this century, identified scientifically described and classified the effects, or levels of achievement of objectives internal and holders Foreign supporters. In addition to the indisputable proven effects in achieving the goals of the operational and intermediate levels, the work is proven and partial achievement of strategic - political (ethno-separatistic) internal target holders of Albanian terrorism in Kosovo and Metohija, defined as secession - the secession of Kosovo and Metohija from the Republic of Serbia. The deployment of international military, security and civilian forces in Kosovo and Metohija, with the temporary transfer of jurisdiction of state authorities of the FRY and Serbia to the security and the UN mission (KFOR and UNMIK) and the EU (EULEX), work has been identified as an indisputable effect of engaging in foreign entities the resolution on the Kosovo issue. In addition, work has confirmed the assumption according to which the set-up and to achieve this strategic objective external entities was primarily based on their "hidden" geopolitical interests, and not to publicly proclaimed goals defined as stopping a "humanitarian catastrophe" in Kosovo and Metohija.